Determinants of Households' Access to Improved Drinking Water Sources: A Secondary Analysis of Eswatini 2010 and 2014 Multiple Indicator Cluster Surveys - Maswati S. Simelane; Mduduzi Colani Shongwe; Kerry Vermaak; Eugene Zwane (Hindawi Limited, 2020)
Worldwide, millions of people still die from diseases associated with inadequate water supply, sanitation, and hygiene, despite the fact that the United Nations recognized access to clean drinking water and sanitation as a human right nearly a decade ago. The objective of this study was to describe the determinants of access to improved drinking water sources in Eswatini in 2010 and 2014. Using the Eswatini Multiple Indicator Cluster Surveys (EMICSs), data for 4,819 households in 2010 and 4,843 in 2014 were analyzed. Bivariate and multivariate complementary log-log regression analyses were conducted to identify the determinants of households' access to improved drinking water sources. The study found that households' access to improved drinking water sources significantly improved from 73.1% in 2010 to 77.7% in 2014 (p<0.0001). In 2010, households whose heads were aged 35-54 and 55 years had lower odds of having access to improved drinking water sources than those with younger ones. In 2014, female-headed households had lower odds, while, in 2010, sex of the household head was not associated with access to improved drinking water sources. In both years, an increase in the number of household members was negatively associated with access to improved drinking water sources compared to those with fewer members. In both years, the odds of access to improved drinking water sources increased with an increase in the wealth index of the household, and households located in urban areas had higher odds of access to improved drinking water sources compared to those in rural settings. In both years, households from the Shiselweni and Lubombo regions had lower odds of access to improved drinking water sources. The government and its partners should continue to upscale efforts aimed at increasing access to improved drinking water, especially in rural areas, to reduce the disparity that exists between urban and rural households.